Endoscopic biopsies from gastrointestinal carcinomas and their suitability for molecular analysis: a review of the literature and recommendations for clinical practice and research. Issue 2 (12th February 2015) - Hale, Matthew David; Gotoda, Takuji; Hayden, Jeremy David; Grabsch, Heike Irmgard
<x xml:space="preserve">Abstract</x> Endoscopic biopsies (EBs) are the gold standard for diagnosing gastrointestinal carcinoma yet no guidelines address EB use for prognostic and predictive molecular testing. This review summarizes the reported quantity and quality of EBs, their relationship with molecular test failure rates and the resultant concordance between EB and resection specimen. Studies reporting molecular testing on gastrointestinal carcinoma EBs published between 2002 and 2014 were identified. Details regarding EB quantity, quality, tumour content, molecular test failure rates as well as causes and concordance with resection specimens were reviewed. Seventy‐five studies were identified. Eighteen (24%) reported the mean EB number per patient (median: 2.1, range: 1–6.6 EBs). Sixty‐one (81%) reported the frequency of test failure (median: 0%, range: 0–100%). Twenty‐two (29%) investigated EB and resection specimen concordance (range: 0–100%). EB quantity and quality affected neither concordance nor failure rate. In summary, few studies currently report EB quantity, EB quality or EB and resection specimen concordance. Reliable molecular testing in EBs appears achievable, and can be representative of resection specimens. Concordance depends upon the testing methodology and biomarker heterogeneity within the tumour. To improve patient care, EB sampling, processing and reporting requires standardization and needs optimization for each biomarker individually.